A novel process for the synthesis of p‐aminophenol by transfer hydrogenation of nitrobenzene using formic acid as hydrogen source. Issue 5 (14th June 2022) - Jia, Yu; Li, Fang; Zhang, Yisheng; Wang, Zhimiao; Che, Conghui; Xue, Wei; Wang, Yanji
Abstract: p ‐Aminophenol (PAP) was synthesized via the transfer hydrogenation of nitrobenzene (NB) over a Pd/AC + SO4 2− /ZrO2 catalyst using formic acid as the hydrogen source. Pd loading had an obvious effect on the reaction, with an optimal loading of 7 wt.%. The average Pd crystallite size was 3–4 nm, and both Pd 0 and Pd 2+ species were present on the catalyst surface. The relative proportions of Pd 0 and Pd 2+ affected the synthesis of PAP, with higher Pd 2+ concentrations increasing the PAP selectivity. The reaction conditions for PAP synthesis were optimized, and an NB conversion of 69.6% with 38.1% PAP selectivity was obtained. After the same catalyst sample was used four times, the NB conversion decreased from 69.6% to 61.3%, and PAP selectivity decreased from 34.7% to 21.5%. These changes were attributed to the loss of Pd and S from the catalyst.